Distinct pattern of genomic breakpoints in CML and BCR::ABL1-positive ALL: analysis of 971 patients - Hovorkova, Lenka; Winkowska, Lucie; Skorepova, Justina; Krumbholz, Manuela; Benesova, Adela; Polivkova, Vaclava; Alten, Julia; Bardini, Michela; Meyer, Claus; Kim, Rathana; Trahair, Toby N; Clappier, Emmanuelle; et al. (Molecular cancer, 2024)
BACKGROUND: The BCR::ABL1 is a hallmark of chronic myeloid leukemia (CML) and is also found in acute lymphoblastic leukemia (ALL). Most genomic breaks on the BCR side occur in two regions - Major and minor - leading to p210 and p190 fusion proteins, respectively. METHODS: By multiplex long-distance PCR or next-generation sequencing technology we characterized the BCR::ABL1 genomic fusion in 971 patients (adults and children, with CML and ALL: pediatric ALL: n = 353; pediatric CML: n = 197; adult ALL: n = 166; adult CML: n = 255 patients) and designed "Break-App" web tool to allow visualization and various analyses of the breakpoints. Pearson's Chi-Squared test, Kolmogorov-Smirnov test and logistic regression were used for statistical analyses. RESULTS: Detailed analysis showed a non-random distribution of breaks in both BCR regions, whereas ABL1 breaks were distributed more evenly. However, we found a significant difference in the distribution of breaks between CML and ALL. We found no association of breakpoints with any type of interspersed repeats or DNA motifs. With a few exceptions, the primary structure of the fusions suggests non-homologous end joining being responsible for the BCR and ABL1 gene fusions. Analysis of reciprocal ABL1::BCR fusions in 453 patients showed mostly balanced translocations without major deletions or duplications. CONCLUSIONS: Taken together, our data suggest that physical colocalization and chromatin accessibility, which change with the developmental stage of the cell (hence the difference between ALL and CML), are more critical factors influencing breakpoint localization than presence of specific DNA motifs.
Keywords: Chromosome Breakpoints; dospělí; akutní lymfatická leukemie; Female; dítě; Genomic breakpoints; Adult; ženské pohlaví; High-Throughput Nucleotide Sequencing; bcr-abl fúzní proteiny; lidé; chronická myeloidní leukemie; BCR; Male; body zlomu chromozomu; vysoce účinné nukleotidové sekvenování; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Child; mužské pohlaví; ABL1; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Fusion Proteins, bcr-abl; Chronic myeloid leukemia; Acute lymphoblastic leukemia; Humans